2010
DOI: 10.1111/j.1469-7610.2010.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do British Indian children have an apparent mental health advantage?

Abstract: The Indian mental health advantage is real and is specific to externalising problems. Family type and academic abilities mediate part of the advantage, but most is not explained by major risk factors. Likewise unexplained is the absence in Indian children of a socio-economic gradient in mental health. Further investigation of the Indian advantage may yield insights into novel ways to promote child mental health and child mental health equity in all ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 29 publications
3
48
1
Order By: Relevance
“…6,7 Similarly, data from epidemiological surveys of mental health disorder in children suggest that British Indians may have a lower incidence of the types of non-psychotic mental health problems likely to lead to hospital admission. 8 There is, however, a lack of clear evidence for children from other ethnic groups within the Asian category.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Similarly, data from epidemiological surveys of mental health disorder in children suggest that British Indians may have a lower incidence of the types of non-psychotic mental health problems likely to lead to hospital admission. 8 There is, however, a lack of clear evidence for children from other ethnic groups within the Asian category.…”
Section: Discussionmentioning
confidence: 99%
“…One study examined measurement invariance with respect to ethnicity between British Indian and British white children using data from the 1999 and 2004 British Child and Adolescent Mental Health Surveys [50]. All parents completed the English version of the SDQ and the multi-group confirmatory factor analyses provided evidence of acceptable fit to the parent and teacher SDQ across ethnicity.…”
Section: Cultural Validitymentioning
confidence: 99%
“…Twenty-seven studies evaluated the structural validity of the SDQ as specified by Goodman, of which 17 used a CFA and were included (Table 3 and Supplementary file 2, median sample size 1068, range 129-56864) [24,35,38,39,43,[45][46][47][48][49][50][51][52][53][54][55][56]. One study carried out a CFA on each of the SDQ scales and is therefore not included in table 3 [54].…”
Section: Structural Validitymentioning
confidence: 99%
“…Two CFA studies in samples that included children age 4 or 5 have examined DIF by ethnicity using both teacher and parent rated SDQ [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . A UK study with only English versions of the SDQ found invariance between White and Indian sub-samples (Goodman et al, 2010b). A North American study also reported invariance between American English and Spanish language samples, however the baseline fit for each group, required to test invariance, were only marginally adequate (Hill & Hughes, 2007).…”
Section: Introductionmentioning
confidence: 99%